If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -6x = 5 Reorder the terms: -6x + 2y = 5 Solving -6x + 2y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -6x + 2y + -2y = 5 + -2y Combine like terms: 2y + -2y = 0 -6x + 0 = 5 + -2y -6x = 5 + -2y Divide each side by '-6'. x = -0.8333333333 + 0.3333333333y Simplifying x = -0.8333333333 + 0.3333333333y
| 6x^2+30=0 | | 10a-15b= | | 0=-2x+4x+4 | | 152=x+x+2(2x-16) | | x*x+7x=7 | | -0.01*x+60=0 | | 3x+-y=-1 | | -3x+3=6-4x | | V+lwh= | | -0.01*x+60=25 | | x/x+7x=7 | | -3c+11A-5a-11c+9c= | | (XxX)+7x=7 | | 1+6x=4x-11 | | x+7x=7 | | fx=x^2+3 | | -0.1*x+60=25 | | 1-2x(5+x)=7 | | (x+4)(x-2)=112 | | 3u^2-75=0 | | Y^2-2y-13=0 | | 2a-5(a+1)=0 | | 3a+2a-a=24 | | x(x+5)-10=x^2-2x+4 | | 2b-7=21 | | h+5h-3-6h=0 | | 3-3n=-27 | | 10-8y+(-13)+12y+8-6y= | | 8(-8)+7y=56 | | 2(2x-6)+2(x+3)=24 | | 12m+9-2m-16=0 | | x+2=-34+5x |